Complex Transitions of Early Career Academics (ECA): A Mixed Method Study of With Whom ECA Develop and Maintain New Networks - Rienties, Bart; Hosein, Anesa (Frontiers in Education, 2020)
The purpose of this article is to explore how Early Career Academics (ECAs) cope with their complex and multiple transitions when starting their new role. By focussing on the participants’ lived experiences in a professional development (PD) training programme to discuss and share practice, we explored how ECAs developed and maintained social network relations. Using social network analysis (SNA) with web crawling of public websites, data was analysed for 114 participants to determine with whom they shared practice outside PD (i.e., external connectors), the seniority of these connectors, and similarity to their job area. The results highlight that ECA networks were hierarchically flat, whereby their sharing practice network of 238 external connectors composed of their (spousal) partner and (male) colleagues at the same hierarchical level. The persons whom ECAs were least likely to discuss their practice with were people in senior management roles. The results of this study highlight that the creation of a community of practice for discussing and sharing of practice from PD programmes appear to be insular. Activities within the organisation and the formation of learning communities from PD may become lost as most of the sharing of practice/support comes from participants’ partners. Organisations may have to create spaces for sharing practice beyond the PD classroom to further organisational learning.